Concept Mapping Strategy through Hybrid Flexible Course: Its Significance toward Student Achievement - K Kiswati; Rosi Anjarwati (English Learning Innovation (englie), 2022)
The pandemic era pushed teachers to switch their teaching methods into online learning. The concept mapping strategy was one of the most effective  teaching  strategies  for  teaching English in face-o face mode .  Is  the concept  mapping  strategy  still  effective  in  online  learning mode?  This  study  utilized  a  quantitative  approach  to  compare  the  use  of   concept  mapping  strategy  and  conventional  strategy.  Both  classes  did  the  instruction  through  hybrid  flexible  course. To obtain the data, test and observation were used. ANCOVA  was  performed  to   analyze  the  data  to  get  the  specific  data  concern  to  the  effect  of  the  strategy  to  the  student  grade.  The  findings  showed  that  in  the  hybrid  flexible  course,  concept  mapping  strategy  did not impact the  students’  achievement,  but  from the observation, it  did  impact  the  students’  motivation  and  activity  during  the  instruction. It can be concluded that there is no significant difference of using concept mapping strategy and conventional strategy through hybrid flexible course